Problems of Vision and Mission and the Dichotomy of Knowledge in Islamic Education - Dumyati (Maklumat: Journal of Da'wah and Islamic Studies, 2023)
Vision and mission are important elements in shaping the identity and direction of an organization. The vision sets long-term goals, while the mission determines the strategic steps to achieve them. However, sometimes complexity arises when implementing the vision and mission, especially when there are differences in the scientific paradigm called the dichotomy of science. The dichotomy of science involves a distinction between seemingly contradictory scientific concepts, such as qualitative vs. quantitative approaches, theory vs. practice, and other scientific disagreements. This challenge can have an impact on the implementation of the vision and mission of an organization and the advancement of science in it. This study aims to investigate the complex relationship between organizational vision and mission with the dichotomy of science.  This research uses qualitative methods with literature review, collecting data from books by Buya Hamka and other papers that discuss it. Through a deep understanding of the role of vision and mission in the context of science dichotomy, this research provides valuable insights for decision makers and organizational leaders. Analysis of the complex relationship between vision and mission with the dichotomy of science aims at helping to design holistic and effective strategies to achieve organizational goals, while advancing knowledge in the field in question.